قرۃالعین حیدر کے ناول "آخر شب کے ہم سفر" میں اماکن کا تذکرہ: Enumeration of places in Quratulain Haider’s Novel "Akhir Shab kay Humsafar" (Al-Qamar, 2023)
Quratulain Haider is one of the most celebrated authors of urdu literature. Though her magnum opus "Aag ka darya" is the most renowned novel of urdu language but her other writings are no less. "Akhhir shab kay hamsafar" is also an excellent depiction of exceptional piece of literature by this literary Giant. This novel was not only contemporary at the time of writing but also represents the authentic eye witnessed accounts of the partition of Bengal in 1971. Scores of places and institutions stated in this novel make this account more authentic and closer to reality. In this article all these places and institutions and their political and geographical importance is been discussed and hereby thus this article proves the importance of places and buildings in a piece of literature moreover this article also provides proofs of historical accuracies in Haiders novels.
Keywords: Quratulain Haider; Bengal; Novel; Akhir-shab kay Humsafar; Historical; Partition Literature; Buildings; Rabindranath TagorePartition Literature; Geographical literature; Rabindranath Tagore